Subjective Social Status and Cardiovascular Reactivity: An Experimental Examination - Pieritz, Karoline (Front Psychol, 2016)
The present experiment examined the causal influence of subjective social status (SSS) on variables related to cardiovascular health [i.e., blood pressure, heart rate variability (HRV)]. Participants were randomly assigned to one of two conditions involving a social comparison that either induced a temporary shift toward high SSS or toward low SSS. Cardiovascular variables were measured before (baseline), throughout, and after the manipulation (recovery). Participants in the low SSS condition had a significantly lower HRV during experimental manipulation than at baseline (p = 0.001). They also showed a significantly stronger HRV reactivity compared to participants in the high SSS condition (p = 0.027). Our results suggest that already temporary shifts of one's SSS have measureable effects on cardiovascular variables. They support the notion that social status plays a causal role in the development of cardiovascular disease.